177k views
3 votes
Please help !!!!! I’m begging you

Please help !!!!! I’m begging you-example-1

2 Answers

7 votes

Answer:

A)

Explanation:

Turn the equation back into x values:


x^(2) -4x-5

-5 and 1 are multiples of -5 and add to get -4


(x-5)(x+1)

Set them equal to 0 and simplify:


(x-5)(x+1)=0\\\\x=5, -1

User Chuprin
by
4.4k points
5 votes

Answer:

the answer is option A.

Explanation:

if u solve for x in the equation using quadratic formula or factorisation u will get x=5 or x= -1

User Abdullah Shah
by
5.2k points